Invariant Subspaces of Collectively Compact Sets of Linear Operators - Mısırlıoğlu, Remzi Tunç; Şafak, Alpay (SP Birkhäuser Verlag Basel, 2008)
In this paper, we first give some invariant subspace results for collectively compact sets of operators in connection with the joint spectral radius of these sets. We then prove that any collectively compact set M in algΓ satisfies Berger-Wang formula, where Γ is a complete chain of subspaces of X.
Keywords: Invariant subspace; collectively compact set; joint spectral radius